Benefit incidence analysis, needs and demography. Measurement issues and an empirical study for Kenya - Isis Gaddis; Lionel Demery (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2012)
Benefit incidence analysis is an extremely popular tool to assess the distribution of benefits from government expenditure in developing countries, particularly in the social sectors. The analysis describes the welfare impact of public spending on groups of people or households, typically along the income distribution. While benefit incidence analysis has generated useful insights into the distribution of benefits from public spending in a variety of sectors, many studies fail to take into account differences in needs for public services across population groups. This can lead to an inappropriate and potentially misleading assessment of equity in public spending. This article reviews the evidence and introduces techniques to account better for heterogeneous needs in benefit incidence analysis. Using the example of an empirical benefit incidence study of education expenditure in Kenya, we show that our understanding of the distributional implications of public spending is greatly improved if we account for demographic differences between population groups.
Keywords: D3; I2; I3; H4; 330; Benefit incidence; public spending; education; demography; population-normalization; stochastic dominance; Kenya